The patent rights, its organization in the scientific projects in physical culture - Benito Rodríguez-Marrero (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
Rome is where the idea of property is forged. Precisely the Renaissance Italian is considered the cradle of the intellectual property system. A law 1474 Venetian is the first systematic attempt to protect a kind of inventions by patent, granted for the first time exclusive rights. This idea goes through different times, from one in which the family or gens had a primitive law on the ground, having in front of it to pater families, who held the power, their full civil rights (sui iuris). This is increased at the beginning of the Republic at the mercy of the conquests, which allowed to confiscate land and give it to individuals against payment of a fee annual.